FLOTATION-ASSISTED HOMOGENEOUS LIQUID-LIQUID MICROEXTRACTION FOR TRACE DETERMINATION OF URANIUM IN WATER SAMPLES BY ICP-MS - Veyseh, Somayeh; Niazi, Ali (Journal of the Chilean Chemical Society, 2017)
In this study, a novel method based on floatation assistance of homogeneous liquid-liquid microextraction (FA-HLLME), combined with inductively coupled plasma-mass spectroscopy (ICP-MS) was proposed, for the determination of trace uranium in environmental water samples. As one of the miniaturized separation and extraction techniques, homogenous liquid–liquid microextraction (HLLME) has been widely applied in the field of environmental monitoring and assessment. 1,2-pyridylazo-2-naphthol (PAN) was used as the complexing agent while toluene and methanol were selected as the extraction and homogeneous solvents, respectively. The factors that influenced the extraction efficiency for uranium determination (including pH, extraction and homogeneous solvents, concentration of PAN and NaCl, extraction time) were studied statistically. Under optimum conditions (pH=7.0, 100 mL toluene, 500 mL methanol, 6.4×10-5 mol L-1 PAN, 1.5 mol L-1 NaCl and 60 sec of extraction time), the linear dynamic range for uranium determination was 1.0-500.0 ng L-1 (R2=0.9995), with a corresponding limit of detection (LOD) of was 0.27 ng L-1. The relative standard deviation (R.S.D.) (C=50.0 ng L-1, n=9) was 1.13%, with a corresponding enrichment factor of 360 for uranium extraction. The proposed method was successfully applied for the determination of uranium in different water samples.